Plant cover diversity and land use impacts on spatial distribution of chemical soil properties using GIS - Bassem H. Mohsin; Salloom B. Salim (Journal of Kerbala for Agricultural Sciences, 2025)
This study aims to investigate the effects of the difference in vegetation cover and land use on spatial distribution of soil electrical conductivity (EC), cation exchange capacity (CEC) and soluble ions. Soil samples from sixty sites were randomly selected on 14585 hectares area located at Algadwal Algharby in Karbala Governorate. Soil samples were collected to a depth of 0-0.3 m, air dried, ground and passed through a 2 mm sieve for laboratory analysis. The results showed that the EC values ranged from ( 1.02 to 53.40) dS m-1 and were greater in the fallow soil than the EC of soils with plant cover. Values of CEC ranged from (12.35 to 32.75) cmol+.kg-1 where lower CEC values were obtained under fallow soils compared to cultivated soils. Generally the coefficients of skewness and kurtosis revealed highly skewed distribution with leptokurtic and platykurtic distributions for the studied characteristics. Geostatistical parameters of the fitted semivariogram models resulted mostly in strong spatial dependence and circular matching model. The fallow soils contents from soluble ions were greater than that of the plant-covered soils due to increasing salinity.